HUBUNGAN KADAR HEMOGLOBIN DAN IMT DENGAN SIKLUS MENSTRUASI PADA REMAJA DI SMPN 01 KEPENUHAN HULU - Nana Aldriana; Andriana; Rahmi Fitria; Putri Aulia Ulfa (Maternity and Neonatal : Jurnal Kebidanan, 2023)
Menstruation is periodic bleeding from the uterus accompanied by shedding of the uterine wall. The normal menstrual cycle is 24-32 days. Hemoglobin is a component of erythrocytes, whose function is to bind oxygen and deliver it to all cell tissues in the body. Body mass index (BMI) is used to indicate normal, overweight, or underweight categories of body weight. The purpose of this study was to determine the relationship between hemoglobin levels and BMI with the menstrual cycle at SMPN 01 Kepuhan Hulu. This type of research is a quantitative analytic research with a cross sectional design, data analysis using chi square. The sample in this study amounted to 82 respondents, who were selected by saturated sampling technique. Data is collected by researchers doing their own examination. The results of univariate analysis based on normal menstrual cycles were 43, menstrual cycles were not normal 39. Body mass index was not normal 45, BMI was normal 37, and hemoglobin levels were anemic 16, and Hb levels were not anemic/normal 66. Results of bivariate analysis there was a relationship between hemoglobin levels with the menstrual cycle with a p value of 0.030 (<0.050) and for BMI with menstrual cycles there is also a relationship with a p value of 0.023 (<0.050). In conclusion, in a study conducted on 82 adolescents, it was found that 39 respondents had abnormal menstrual cycles. Respondents who were anemic were 66 people. There were 45 respondents who had an abnormal BMI. The researchers also found that there was a significant relationship between hemoglobin levels and the menstrual cycle and there was a significant relationship between BMI and the menstrual cycle.